2020
DOI: 10.1186/s12950-020-0235-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity ultrasound attenuates paw edema formation and decreases vascular permeability induced by carrageenan injection in rats

Abstract: Background: Therapeutic potential of low-intensity ultrasound (LIUS) has become evident in various musculoskeletal diseases. We have previously shown that LIUS has an inhibitory effect on local edema in various diseases including the arthritis and brain injury. In this study, we examined whether LIUS can attenuate paw edema formation vis-à-vis vascular permeability and inflammation in rats induced by carrageenan. LIUS with a frequency of 1 MHz and the intensities of 50, 100, or 200 mW/cm 2 were exposed on rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
19
0
2
Order By: Relevance
“…In addition, various signaling molecules and enzymatic pathways participate in driving the inflammation, including cyclooxygenase 2 (COX-2), a crucial enzyme that regulates the synthesis of prostaglandins (PGs) during inflammation [12]. In addition, TNF-α and interleukin 1 beta (IL-1β) were investigated as the essential main mediators that contribute to acute and chronic inflammation [13]. Reactive oxygen species (ROS) play a critical role in cellular defense systems as they are secreted by the inflammatory cells and exacerbate the oxidative stress process [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various signaling molecules and enzymatic pathways participate in driving the inflammation, including cyclooxygenase 2 (COX-2), a crucial enzyme that regulates the synthesis of prostaglandins (PGs) during inflammation [12]. In addition, TNF-α and interleukin 1 beta (IL-1β) were investigated as the essential main mediators that contribute to acute and chronic inflammation [13]. Reactive oxygen species (ROS) play a critical role in cellular defense systems as they are secreted by the inflammatory cells and exacerbate the oxidative stress process [14].…”
Section: Introductionmentioning
confidence: 99%
“…US treatment can also increase neurotrophic factor protein levels to suppress apoptosis and protect nerves in an animal model of traumatic brain injury 40 . Hence, the observed histopathological improvements could provide evidence of anti-inflammatory effects by inducing neurotrophic factors and tissue repair by US stimulation In previous studies, edema and neutrophil infiltration in a rodent model of foot edema were significantly reduced by low-intensity ultrasound stimulation 41,42 . Similarly, we observed the development of edema (Figure S3) and increased levels of inflammatory factors (ED-1, iNOS, and TNF-α; Figure 3) within the SCI area, all of which was reduced following SCIU5 treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, several recent clinical trials and experimental studies have reported that US can elicit an anti-inflammatory response, promote tissue repair, and reduce pain [27][28][29][30] . US stimulation reduces inflammatory mediators, such as cyclooxygenase (COX)-1/2, inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF)-α, and interleukin (IL)-1β, as well as immune cell infiltration, in numerous inflammatory diseases, including peripheral nerve injury [31][32][33] . In particular, Zachs et al demonstrated that daily US stimulation targeting the spleen could induce an anti-inflammatory response via immunomodulation of both T and B cells, conferring protective and therapeutic effects in inflammatory arthritis 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The main signs of in ammation appear immediately after subcutaneous injection-edema, hyperalgesia and erythema, which are caused by the action of pro-in ammatory agents-bradykinin, histamine, tachykinin, complement and reactive oxygen species as well as nitrogen substances 19 . Peripheral edema is known to be mainly caused by venous obstruction and increased vascular permeability 20 . Therefore, in this investigation, the changes of paw edema thickness after the injection of λ-carrageenan had been measured to evaluate the anti-in ammation effect.…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory mediators such as histamine and serotonin cause increase of vascular leakage 25 . Moreover, the extravasation of the liquid including plasma proteins will cause the leukocytes aggregation and adhesion, which are important features of acute in ammation 20,22,23 . Jane Jeon et al found that combined application of alloferon-1 and prednisolone to treat asthma signi cantly reduced the number of eosinophils, macrophages, and neutrophils in bronchoalveolar lavage uid (BALF) of asthmatic mice induced by ovalbumin (OVA) 24 .…”
Section: Discussionmentioning
confidence: 99%